I-FinTech Adoption Mediation on the Financial Literacy Elements and Sustainable Entrepreneurship among Bumiputera MSMEs in Malaysia - Basar, Suria Abu; Ibrahim, Noor Ayuernie; Tamsir, Fazilah; Rahman, Asma Rina Abdul; Zain, Noor Nasyikin Mohd; Poniran, Halimi; Ismail, Rina Fadhilah (International Journal of Economics and Financial Issues, 2024)
The term “i-FinTech” refers to businesses or entrepreneurs that integrate modern, Shariah-compliant technologies with financial services. Nevertheless, MSMEs are typically having lack internal knowledge or poor management, incompetent entrepreneurs, and limited financial resources. The purpose of this research is to analyse if financial literacy elements affect i-FinTech adoption and, in turn, promote sustainable entrepreneurship among Bumiputera SMEs in Selangor, Malaysia. A convenience sample strategy was used to disseminate 1,394 surveys to the Bumiputera entrepreneurs, utilizing a quantitative approach. PLS-SEM and mediation analysis are used to analyse the data. The findings indicate that financial literacy and digital financial literacy have a favorable and significant impact on the adoption of i-Fintech. On the other hand, the adoption of i-Fintech is adversely affected by financial management behavior. Furthermore, this study shows that the relationship between financial literacy and digital financial literacy towards sustainable entrepreneurship is mediated in a complimentary way by the adoption of i-FinTech. This result indicates that Bumiputera business owners that are financially and digitally literate are more likely to use i-FinTech and ultimately make a substantial contribution to sustainable entrepreneurship. The results should improve knowledge of the dynamics between the potential of i-FinTech and sustainable entrepreneurship for researchers, regulators, entrepreneurs, and i-FinTech service providers. It is advised that MSMEs keep using i-FinTech to support their operations in order to minimise the effects of a downturn in the market and maintain seamless operations.